GAMBARAN TINGKAT KECEMASAN PESERTA VAKSINASI COVID 19 DI WILAYAH RUMAH SAKIT JIWA NAIMATA KOTA KUPANG - Maryo Jensen Bolla; Yasinta Betan; Fepyani Thresna Feoh (CHMK HEALTH JOURNAL, 2022)
The The COVID-19 pandemic has created new challenges for the state to overcome. In particular, it is about how the state responds and seeks to prevent and stop the spread of the virus much more widely. Vaccination is considered as one of the solutions in an effort to overcome the covid-19 pandemic. The implementation of the covid-19 vaccination that occurred in the community caused a level of anxiety which of course disrupted the vaccination process. People who are prone to anxiety have the potential to be disturbed by the vaccination process because of the stress caused by the anxiety they have before and after the vaccination participants in the Naimata Mental Hospital, Kupang City. This study was a descriptive study using the Accidental Sampling technique with 29 respondents, the data collection instrument was using a questionnaire. The result showed that most of the respondents had no anxiety about vaccination (normal) 26 people (89,76%) and 3 people mild anxiety (10,3%). From the results of the study, it was stated that some of the vaccination participants did not have any anxiety about the covid-19 vaccination because people were starting to realize the importance and benefits of vaccination. Although the covid-19 vaccination has been running for quite a while, but there are still those who feel anxious about the covid-19 vaccination, the anxiety experienced by the respondents in this study is a natural thing that can happen considering the current state of the covid-19 pandemic that has not yet occurred. Been experienced by the community before. Keyboard: Covid-19, Covid-19 Vaccination and Anxiety)